Analisis Laporan Keuangan Pada PT. Bank SULUT di Manado. - Ontorael, Rizal; Montolalu, Jhonny; Manoppo, Wilfried Seth (JURNAL ADMINISTRASI BISNIS (JAB), 2014)
The company's performance is a picture of the financial condition of a company that is analyzed using the tools of financial analysis, so that can be known about the good and bad of a situation that reflects the performance of the company in the form of a certain period. Every company needs a policy of good corporate financial management, to realize the goals to be achieved by each company. One aspect to consider is how to manage the financial company which is good because the financial management of the company prepare a financial report will describe the activities of the company during a specific period. Financial ratio analysis is a number obtained from a financial statement items with more posts that have relevant and significant relationship. Assessment of performance is to measure the extent to which the performance of an organization in all aspects. The results obtained from the year 2010 up to 2012 the company's performance is unstable, wherein in the calculation of liquidity ratios appear that the company is still not enough liquid in paying any obligations to depositors. So is the solvency ratio was evident after analysis of the year 2010 up to 2012 clearly states that the company is still very dependent on his debts, therefore, the financial manager is required to properly mengola this ratio so as to balance control with a high level risks faced. From the research that is particularly Profitability ratios proved very stable achievement of the year where 2010sampai with increased earnings in 2012. So the company considered successful in getting profit from operations. Keywords: Financial Ratio Assessment Tool, Financial Performance